2017
DOI: 10.1186/s13104-017-3005-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a suitable reference gene for quantitative gene expression in mouse lymph nodes after vaccination

Abstract: BackgroundThe quantification of gene expression is an important tool in the evaluation of the immune response to vaccines. Reliable reference genes for gene expression studies in mouse draining lymph nodes after vaccination have not been reported.ResultsThe utility of seven potential reference genes was investigated using commercially available Taq-man primer/probe mixes. Results were evaluated with RefFinder, a web-based program including multiple algorithm methods such as geNorm, NormFinder, BestKeeper and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Top 15 candidate reference genes with the lowest CV values are all annotated proteins, and most of them have been widely studied in model organisms. For example, UBC has been identified as a reliable reference gene in some organisms [26][27][28]. By GO enrichment analysis of all candidate reference genes, as expected, candidates are highly enriched in biological process associated with metabolic process, cellular metabolic process, and protein metabolic process, suggesting they may play an essential part in maintenance of basal cellular functions, as described in other organisms of human, mouse, maize, and scallop [29][30][31].…”
Section: Stability Analysis Between Candidates and Commonly Used Refesupporting
confidence: 61%
“…Top 15 candidate reference genes with the lowest CV values are all annotated proteins, and most of them have been widely studied in model organisms. For example, UBC has been identified as a reliable reference gene in some organisms [26][27][28]. By GO enrichment analysis of all candidate reference genes, as expected, candidates are highly enriched in biological process associated with metabolic process, cellular metabolic process, and protein metabolic process, suggesting they may play an essential part in maintenance of basal cellular functions, as described in other organisms of human, mouse, maize, and scallop [29][30][31].…”
Section: Stability Analysis Between Candidates and Commonly Used Refesupporting
confidence: 61%
“…Therefore, when such a great variation is observed on the genes ranked by different tools, there is no recommendation of the best method to select the genes, as well as there is no standard score or threshold indicating good or bad stability. Mosley et al (2017) [ 37 ], after analyzing 5 tools (BestKeeper, geNorm, NormFinder, DeltaCt and RefFinder), concluded that the geNorm seems to be the best tool for choosing the most reliable genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a great variation in the classification of genes by different software, there is no recommendation for the best method of gene selection, nor a pattern that indicates good or poor stability [46]. After the analysis with BestKeeper, geNorm and NormFinder, the geNorm seemed to be the most suitable software to choose the most reliable genes, because its results were more similar to those found with RankAggreg.…”
Section: Plos Onementioning
confidence: 96%